SCALE-UP OF PHENOLIC COMPOUNDS PRODUCTION FROM Styrax paralleloneurum LEAVES AND EXTRACT PURIFICATION USING AMBERLITE XAD-2 - Martgrita, Merry Meryam; Sianipar, Imelda Febrika; Manurung, Adelina (BRIN - Badan Riset dan Inovasi Nasional, 2024)
The current study aimed to determine the total phenolic compound content, antioxidant activity, and antibacterial activity of fermented Styrax leaf extract in 2000 mL volume. Fermentation by Aspergillus niger was carried out for 64 hours. After extraction, purifi-cation was conducted using Amberlite XAD-2 resin in ion exchange chromatography. The total phenolic content of the unpurified extract was 92.75 mg GAE.g-1, while the purified extract was 146.67 mg GAE.g-1. Antioxidant activity expressed in IC50 values was 31.71 ppm for the unpurified extract and 14.11 ppm for the purified extract. The antibacterial activity tested on Staphylococcus aureus and Pseudomonas aeruginosa showed an inhibition zone diameter of 31.43 mm and 28.2 mm, respectively for the unpurified extract, while for the purified extract 33.96 mm and 35.5 mm, respectively. It can be concluded that the purification of fermented Styrax leaf extract caused a stronger antioxidant activity and a very potent antibacterial activity.